Genetic diversity of Burmese grape (Baccaurea ramiflora Lour.) cultivars and Ha Chau cultivar identification based on DNA barcodes (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khang DT, Huy TG, Thi NPA, Quyen DTH, Nhu NTB, Binh BN, Men TT, Dung TN. 2022. Genetic diversity of Burmese grape (Baccaurea ramifloraLour.) cultivars and Ha Chau cultivar identification based on DNA barcodes. Biodiversitas 23: 3513-3520. Burmese grape (Baccaurea ramiflora Lour.) is an underutilized fruit tree in the Mekong Delta and has the potential for food sources as well as landscape plants,especially Ha Chau cultivar. It has been considered an indigenous plant in Can Tho city, Vietnam with specific taste. However, their genetic diversity, utilization,and identification have not been dealt with in-depth. This study aimed to characterize genetic diversity among the five cultivars of Burmese grape in the Mekong Delta and to distinguish Ha Chau from other cultivars based on DNA barcodes, namely matK, rbcL, ycf1b, rpoC1, psbK-I, atpF-H,and ITS. DNA of twelve individuals belong to five Burmese grape cultivars was extracted prior to further amplification and sequencing. Sequences were analyzed to detect variable sites and the phylogenetic tree was constructed by the Maximum Likelihood method. Based on substitution sites and indel mutations, the plastid intergenic spacer atpF-H and ycf1b gene reflected the genetic diversity in five Burmese grape cultivars. Moreover, these sequences were valuable DNA barcodes for discrimination of Ha Chau cultivar. In combination of four markers (rbcL, rpoC1, ycf1b, and psbK-I) for phylogenetic construction, our finding revealed that Ha Chau cultivar is closely related to Red cultivar with highly supported bootstrap value of 89%. Such data could be applied for reliable identification of Ha Chau cultivar from other B. ramiflora cultivars in plant authentication.